Correlación entre la depuración de creatinina con la albúmina sérica y proteínas en orina de 24 horas en pacientes adultos con enfermedad renal crónica - Villacorta Rodríguez, Nilton Renzo (2015)
The evaluation of patients with chronic kidney disease (CKD) should include the estimated glomerular filtration, urine sediment and determination of albuminuria in the urine. The calculations of creatinine clearance, serum albumin and protein in urine 24 hours pathophysiological correlate, however there are no studies that correlate the variables under study found. Method: This is a (retrospective) correlational descriptive study, the sample consisted of 62 patients diagnosed with chronic kidney disease. To assess the association between variables the Spearman correlation factor, with a confidence level of 95% was used, considering significant when p≤0.05. Results: Mean age was 15.8 ± 64.6 years (range: 42-89 years) for men and an average of 63.8 years for women. The percentage of men with CKD (55%) is higher than that of women (45%) with this same disease. A slight direct relationship between creatinine clearance and albumin but not significant (p-value> 0.05), however note that the relationship is reversed for high values of creatinine clearance values of protein in urine of 24 found hours tend to decrease, being statistically significant (p-value <0.05). Conclusion: The correlation of creatinine clearance proteins in urine of 24 hours is inverse and significant; however with albumin it is direct but not significant